“Missed” Diagnosis of Mycosis Fungoides: A Case Report - Mahesh Mathur; Neha Thakur; Sandhya Regmi; Supriya Paudel; Sambidha Karki; Nabita Bhattarai (Clinical Case Reports)
ABSTRACT Mycosis fungoides (MF) is the most common subtype of primary cutaneous T‐cell lymphoma characterized by malignant proliferation of T cells with epidermotropism in the skin. MF has an indolent course, presents as erythematous scaly patches or plaques, and may progress to generalized erythroderma, cutaneous tumors, or extracutaneous invasion. MF is often misdiagnosed at early stages due to nonspecific clinical findings. Patients with MF are at high risk for developing secondary malignancies, including hematological malignancies. We hereby report a case of MF misdiagnosed and associated with underlying diffuse large B‐cell lymphoma.